2018
DOI: 10.1111/imj.13698
|View full text |Cite
|
Sign up to set email alerts
|

High urinary interleukin‐8 levels is associated with poor prognosis in idiopathic membranous nephropathy

Abstract: Biomarkers required to assess accurately the prognosis of idiopathic membranous nephropathy (IMN) are still unavailable. A retrospective study on 156 IMN patients showed only urinary IL-8 was associated with the achievement of initial complete remission (CR) in IMN patients. A urinary IL-8 level of less than 61.25 pg/mL was more sensitive for prediction of CR in IMN patients. Therefore, urinary IL-8 may be a potential biomarker for evaluating short-term prognosis of IMN patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…These include anti-phospholipase A2 receptor (PLA2R), nuclear factor NF-kappa-B p105 subunit (NFKB1), interferon regulatory factor 4 (IRF4), and human leukocyte antigen (HLA). [ 24 ] At the same time, Jilin Chen et al [ 25 ] conducted a retrospective cohort study and found that CXCL8 was highly correlated with the prognosis of MN;MMP9, MMP2 and TGFB1 are significantly expressed in patients with MN, which can be used as diagnostic markers of MN. MMP9 is significantly correlated with proteinuria, and MMP9 is significantly increased in patients with proteinuria in nephropathy [ 26 , 27 ] ; Studies have found that glomerular inflammation in MN lesions has different signaling pathways, and PTGS2 and monocytes/macrophages are involved in the inflammatory process of nephritis [ 28 ] ;Tumor necrosis factor (TNF), a pleiotropic cytokine with proinflammatory and immunomodulatory properties, has an important role in renal disease, which predicts renal progression in patients with MN [ 29 ] ;Immunohistochemistry confirmed the high expression of VEGFA in MN renal biopsy specimens.…”
Section: Discussionmentioning
confidence: 99%
“…These include anti-phospholipase A2 receptor (PLA2R), nuclear factor NF-kappa-B p105 subunit (NFKB1), interferon regulatory factor 4 (IRF4), and human leukocyte antigen (HLA). [ 24 ] At the same time, Jilin Chen et al [ 25 ] conducted a retrospective cohort study and found that CXCL8 was highly correlated with the prognosis of MN;MMP9, MMP2 and TGFB1 are significantly expressed in patients with MN, which can be used as diagnostic markers of MN. MMP9 is significantly correlated with proteinuria, and MMP9 is significantly increased in patients with proteinuria in nephropathy [ 26 , 27 ] ; Studies have found that glomerular inflammation in MN lesions has different signaling pathways, and PTGS2 and monocytes/macrophages are involved in the inflammatory process of nephritis [ 28 ] ;Tumor necrosis factor (TNF), a pleiotropic cytokine with proinflammatory and immunomodulatory properties, has an important role in renal disease, which predicts renal progression in patients with MN [ 29 ] ;Immunohistochemistry confirmed the high expression of VEGFA in MN renal biopsy specimens.…”
Section: Discussionmentioning
confidence: 99%